Writing Skill Learning Strategies among Non- Native Arabic Speakers in Jordan - Alkhawaldeh, Mohammed Ali; Barasneh, Thaer Bassam (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to, at determine the most common, frequently writing learning strategies among non-native Arabic speakers in Jordan and whether differences in their use according to variables like gender and study level were statistically significant. Methods: The researchers developed a scale of thirty items, divided into cognitive, metacognitive, and socio-affective strategies, to accomplish the study’s objectives. The measure was used with (120) Chinese undergraduate students at Jordanian and Yarmouk universities studying Arabic language and its literature. Results: According to the study’s findings, socio/affective techniques were used by high-level students more frequently than cognitive and meta-cognitive ones. The findings also indicated that there was a statistically significant difference due to the gender variable on students’ rates of socio-affective strategies in learning writing skill, favoring females, and that there was a statistically significant difference due to the study level on their rates of cognitive and meta-cognitive strategies, favoring third-year students and above, but less favoring second-year students in socio-affective strategies. Conclusions: Several recommendations were made in light of the study’s findings, including urging non-Arabic speakers to adopt writing skill learning strategies, particularly cognitive and metacognitive ones.